Peran Konselor Dalam Meningkatkan Sumber Daya Manusia Di Smk Al-Washliyah Melalui Layanan Bimbingan Dan Konseling - Hadi Lubis, Riswan (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This research uses the method. Data was collected using observations and interview techniques. In analyzing data researchers used qualitative analysis techniques with steps of data exposure, data reduction, and drawing conclusions. The problem in this study is the low level of human resources in Al-Washliyah senior high school.The objectives of this study are 1) what is the cause of the low level of human resources in Al-Washliyah senior high school. 2) counseling guidance theachers efforts in increasing student learning interest in order to improve the human resources at Al-Washliyah senior high school. 3) how to create a high quality tablespoons at Al-Washliyah senior high school. 4)what are the supporting and inhibithing factors of the guidance counseling theacher in increasing the tablespoons at Al-Washliyah senior high school.Based on the results of the study it was found that the level of human resources in Al-Washliyah senior high school was not good enough. This was based on many things. One of them was due to the lack of awareness of the importance of quality human resources in school facilities that did not support the lack of motivation and enthusiasm of students in learning which resulted in human resources in Al-Washliyah senior high school.